Efficient production of metal manganese achieved by cylindrical and rotary electrode. (1st December 2021) - Luo, Shuliang; Guo, Huajun; Zhang, Shukai; Wang, Zhixing; Li, Xinhai; Peng, Wenjie; Wang, Jiexi; Yan, Guochun
Abstract: Electrowinning is a vital process for the production of metal manganese, however, always suffer from low cathodic current efficiency and nodule issues. Herein, a new concept involving cylindrical cell and rotary electrolysis is proposed and demonstrated for manganese electrowinning process. Results indicate that manganese deposits on cylindrical cathode are uniform and the edge effect is effectively suppressed. The cathodic current efficiency increases from 77.65% to 82.56% and the corresponding energy consumption decreases from 5.29 kWh/kg to 4.27 kWh/kg with the comparison of traditional plate electrolytic cell. Based on the above results, fluid field is further introduced by stirring catholyte and rotating cathode respectively. The fluid field can refine manganese grains and significantly inhibit the formation of manganese nodules. Under the proper cathode rotating speed, the cathodic current efficiency reaches 86.22% and ideal compact flat electrolytic manganese flakes can be obtained. Our strategy here may also inspire other researchers especially in electrochemical fields to improve energy and mass efficiencies for a bubble-involving chemical process. Graphical abstract: Cylindrical electrode was applied to manganese electrowinning process, boosting both energy and mass efficiencies for this bubble-involving reaction. Image 1